Los protocolos de Úbeda (1506-1507) y de Baeza (1512). Regesta de su contenido e índices - Porras Arboledas, Pedro Andrés (Cuadernos de Historia del Derecho, 2007)
The two older complete protocols of the Baeza and Úbeda archives are presented in this contribution. Joint to the 1516 protocol already published, they allow an approach, from their rich appendices, to the 16th century society and people around the Jaen area.